Kinetic and Structural Evidences on Human Prolidase Pathological Mutants Suggest Strategies for Enzyme Functional Rescue - Besio, Roberta; Gioia, Roberta; Cossu, Federica; Monzani, Enrico; Nicolis, Stefania; Cucca, Lucia; Profumo, Antonella; Casella, Luigi; Tenni, Ruggero; Bolognesi, Martino; Rossi, Antonio; Forlino, Antonella (PLOS ONE, 2013)
Prolidase is the only human enzyme responsible for the digestion of iminodipeptides containing proline or hydroxyproline at their C-terminal end, being a key player in extracellular matrix remodeling. Prolidase deficiency (PD) is an intractable loss of function disease, characterized by mutations in the prolidase gene. The exact causes of activity impairment in mutant prolidase are still unknown. We generated three recombinant prolidase forms, hRecProl-231delY, hRecProl-E412K and hRecProl-G448R, reproducing three mutations identified in homozygous PD patients. The enzymes showed very low catalytic efficiency, thermal instability and changes in protein conformation. No variation of Mn(II) cofactor affinity was detected for hRecProl-E412K; a compromised ability to bind the cofactor was found in hRecProl-231delY and Mn(II) was totally absent in hRecProl-G448R. Furthermore, local structure perturbations for all three mutants were predicted by in silico analysis. Our biochemical investigation of the three causative alleles identified in perturbed folding/instability, and in consequent partial prolidase degradation, the main reasons for enzyme inactivity. Based on the above considerations we were able to rescue part of the prolidase activity in patients’ fibroblasts through the induction of Heath Shock Proteins expression, hinting at new promising avenues for PD treatment.